Performance investigation of a lab–scale latent heat storage prototype – Numerical results. (1st March 2017) - Niyas, Hakeem; Prasad, Sunku; Muthukumar, P.
Highlights: Developed a numerical tool for analyzing a shell-and-tube LHS system. Effective heat capacity method is used for incorporating the latent heat. Number of heat transfer fluid tubes and fins are optimized. Partial charging/discharging is efficient than complete charging/discharging. Numerically predicted values match well with the experimental results. Abstract: In the current study, numerical analysis of the charging and discharging characteristics of a lab-scale latent heat storage (LHS) prototype is presented. A mathematical model is developed to analyze the performance characteristics of the LHS prototype of shell and tube heat exchanger configuration. Effective heat capacity (EHC) method is implemented to consider the latent heat of the phase change material (PCM) and Boussinesq approximation is used to incorporate the buoyancy effect of the molten layer of the PCM in the model. For proper modeling of velocities in the PCM, Darcy law's source term is added. The governing equations involved in the model are solved using a finite element based software product, COMSOL Multiphysics 4.3a. The number of embedded tubes and fins on the embedded tubes are optimized based on the discharging time of the model. Various performance parameters such as charging/discharging time, energy storage/discharge rate and melt fraction are evaluated. Numerically predicted temperature variations of the model during charging and discharging processes were compared with the experimental data extracted from the lab-scale LHS prototype and a good agreement was found between them.